The immaturity of patient engagement in value-based healthcare—A systematic review - van der Voorden, Michael; Sipma, Wim S.; de Jong, Margriet F. C.; Franx, Arie; Ahaus, Kees C. T. B. (Frontiers in Public Health, 2023)
Introduction: In recent years, Value-Based Healthcare (VBHC) has been gaining traction, particularly in hospitals. A core VBHC element is patient value, i.e., what matters most to the patient and at what cost can this be delivered. This interpretation of value implies patient engagement in patient–doctor communication. Although patient engagement in direct care in the VBHC setting is well described, patient engagement at the organizational level of improving care has hardly been studied. This systematic review maps current knowledge regarding the intensity and impact of patient engagement in VBHC initiatives. We focus on the organizational level of a continuous patient engagement model. Methods: We performed a systematic review following PRISMA guidelines using five electronic databases. The search strategy yielded 1546 records, of which 21 studies were eligible for inclusion. Search terms were VBHC and patient engagement, or similar keywords, and we included only empirical studies in hospitals or transmural settings at the organizational level. Results: We found that consultation, using either questionnaires or interviews by researchers, is the most common method (17/ 21) to involve patients in VBHC. Higher levels of patient engagement, such as advisory roles, co-design, or collaborative teams are rare. We found no examples of the highest level of patient engagement such as patients co-leading care improvement committees. Conclusions: This study included 21 articles, the majority of which were observational, resulting in a limited quality. Our review shows that patient engagement at the organizational level in VBHC initiatives still relies on low engagement tools such as questionnaires and interviews. Higher-level engagement tools such as advisory roles and collaborative teams are rarely used. Higher-level engagement offers opportunities to improve healthcare and care pathways through co-design with the people being served. We urge VBHC initiatives to embrace all levels of patient engagement to ensure that patient values find their way to the heart of these initiatives.